2015
DOI: 10.1128/iai.00667-15
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of saeRS -Dependent Targets Critical for Protective Humoral Immunity against Staphylococcus aureus Skin Infection

Abstract: Recurrent Staphylococcus aureus skin and soft tissue infections (SSTIs) are common despite detectable antibody responses, leading to the belief that the immune response elicited by these infections is not protective. We recently reported that S. aureus USA300 SSTI elicits antibodies that protect against recurrent SSTI in BALB/c but not C57BL/6 mice, and in this study, we aimed to uncover the specificity of the protective antibodies. Using a proteomic approach, we found that S. aureus SSTI elicited broad polycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Our findings that rsp contributed to lethality in pulmonary disease is also supported by a recent study of cutaneous S. aureus disease (54). In both models, toxins have been shown to be key mediators of disease (13,55). Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Our findings that rsp contributed to lethality in pulmonary disease is also supported by a recent study of cutaneous S. aureus disease (54). In both models, toxins have been shown to be key mediators of disease (13,55). Fig.…”
Section: Discussionsupporting
confidence: 76%
“…First, we have not yet identified the immunodominant epitopes in C57BL/6 mice that outcompete protective responses. We hypothesize that these will come from one or more antigens that elicited strong antibody or T cell responses in C57BL/6 mice, but not BALB/c mice (17). Second, future studies should compare the protection afforded by full-length LukE and LukS-PV with LkT/C or LukE 153-168 -and LukE 185-200 -specific T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that the failure of SSTI to elicit protective anti-Hla antibody responses in C57BL/6 mice was due to the specificity of the MHC haplotype. We previously demonstrated that protective immune responses against S. aureus SSTI in BALB/c mice were directed against sae-regulated antigens, including Hla, LukE, and LukS-PV (11,17). However, while Hla-specific antibody responses correlated with protection, the LukS-PV-and LukE-specific antibody levels did not (Fig.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations